THE INFLUENCE OF MATHEMATICAL DISPOSITION, SELF-EFFICACY, AND LEARNING MOTIVATION ON MATHEMATICS LEARNING ACHIEVEMENT - Baso Intang Sappaile; Norma Nasir; Miske Elsy Sibian (Adisam Publisher, 2025)
This research is a researchex_post facto which aims to determine the influence of mathematical disposition, self-efficacy, and learning motivation. The research population was all students of class X of Madrasah Alyiah Arifah Gowa. Sampling using the techniquerandom sampling. The instrument consists of a scale (mathematical disposition, self-efficacy, and learning motivation) and a mathematics learning achievement test. The research data were analyzed using descriptive statistics and inferential statistics using multiple regression. The results of the study showed that, statistically descriptively: 1) students' mathematical disposition is in the high category; 2) students' self-efficacy and learning motivation are each in the medium category. Statistically inferentially: 1) mathematical disposition, self-efficacy, and learning motivation together have a relationship with the mathematics learning achievement test with Fcount = 18.50 and p_value = 0.0001 < α = 0.005 and the determination coefficient is 49%; 2) partially: (1) mathematical disposition does not have a positive relationship with mathematics learning achievement with tcount = -0.18 and p-value = 0.431 > α = 0.005; (2) self-efficacy has a positive relationship with mathematics learning performance with tcount = 2.96 and p_value = 0.0025 < α = 0.005; (3) learning motivation has a positive relationship with mathematics learning achievement with tcount = 2.90 and p_value = 0.0025 < α = 0.005.